A Novel Photosynthesis of Carboxymethyl Starch-Stabilized Silver Nanoparticles - M. A. El-Sheikh (The Scientific World Journal)
The water soluble photoinitiator (PI) 4-(trimethyl ammonium methyl) benzophenone chloride is used for the first time in the synthesis of silver nanoparticles (AgNPs). A new green synthesis method involves using PI/UV system, carboxymethyl starch (CMS), silver nitrate, and water. A mechanism of the reduction of silver ions to AgNPs by PI/UV system as well as by the newly born aldehydic groups was proposed. The synthesis process was assessed by UV-vis spectra and TEM of AgNPs colloidal solution. The highest absorbance was obtained using CMS, PI and AgNO3 concentrations of 10 g/L, 1 g/L, and 1 g/L, respectively; 40°C; 60 min; pH 7; and a material : liquor ratio 1 : 20. AgNPs so-obtained were stable in aqueous solution over a period of three weeks at room temperature (~25°C) and have round shape morphology. The sizes of synthesized AgNPs were in the range of 1–21 nm and the highest counts % of these particles were for particles of 6–10 and 1–3 nm, respectively.